Evaluation of the Wound Healing Potential of Hypericum triquetrifolium Turra: An Experimental Animal Study and Histopathological Examination - Tamam El-Elimat; Haya S. El-Qaderi; Wael M. Hananeh; Mahmoud M. Abu AlSamen; Ahmed H. Al Sharie; Musa A. Alshehabat; Mohammad Al-Gharaibeh; Feras Q. Alali (Scientia Pharmaceutica, 2023)
The wound healing potential of the aerial parts of Hypericum triquetrifolium Turra (Hypericaceae) was evaluated using an in vivo excision wound model in rats. Adult male Sprague Dawley rats were randomly assigned into seven groups; blank vehicles (olive oil and petroleum jelly), negative control, treatments [H. triquetrifolium ethanolic extract in petroleum jelly (5% and 10%) and H. triquetrifolium olive oil macerate (100 and 200 g/L)], and positive control (MEBO). Treatments were applied topically once daily until the wounds had completely healed. Wound areas and contraction rates were calculated, and full-thickness samples of the healed skin were collected for histopathological examination. H. triquetrifolium ointment (5%) showed the best wound healing activity with statistically significant differences when compared with the MEBO, petroleum jelly, and the negative control groups. Tissue sections were histopathologically examined in terms of re-epithelialization, granulation tissue development, collagen deposition, inflammatory cell infiltration, angiogenesis, and ulcer formation to support the in vivo excision wound model findings. H. triquetrifolium ointment (5%) showed the best histopathological scores in both re-epithelialization and ulcer formation. For quality control purposes, a high-performance liquid chromatography (HPLC) method was used to quantify key marker compounds in the extract, namely hypericin and rutin which showed a content of 0.64% and 4.46% (w/w), respectively. Based on the experimental results, H. triquetrifolium ointment (5%) exhibits remarkable wound healing properties at various stages of the wound healing process. Further investigations to prove its safety and efficacy in different types of wounds and to uncover its cellular mechanisms are warranted.